Construção e potencialidades de um sistema de monitoramento e avaliação para a saúde mental a partir da APS - Albert, Carla Estefanía (2014)
This doctoral study presents three papers about monitoring and evaluation (M&E), based on the concept of care network in Mental Health. The research issues are about differences between the normative indication of evaluation in mental health and their real practice. The first paper is a literature review on mental health assessment. The second it is a narratives analysis applied on interviews of mental health managers. Given those outcomes of initial works, we propose a strategy for process evaluation, projected from care guideline in mental health. Results: The conclusion pronounces a difference between normative, as requested on the National Health System Politics, and the real world of evaluation actions in mental health, its procedures and practices. Even with the recent proposals for federal programs about health evaluation, to building an evaluation network to mental health service, it is a continuous challenge. Now a day, data about mental health service are limited to some governmental indicators. On the micro political space of Health, the reality of M&E revealed that activities were sporadic and characterized by direct participation of Health workers to carry them out.